2016
DOI: 10.13080/z-a.2016.103.026
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Pseudomonas syringae pvs. from different host plants by repetitive sequence-based PCR and multiplex-PCR

Abstract: Pseudomonas syringae pvs., isolated from different cultivars of sweet cherry grown in several locations in Serbia, were characterized and compared with strains collected earlier from sour and sweet cherry and oil pumpkin growing in this region, as well as with reference strains P. syringae pv. morsprunorum race 1 CFBP2119, P. s. pv. lachrymans 765R and P. s. pv. syringae H-1. By employing LOPAT and GATTa tests, isolates were identified as P. syringae pv. syringae and P. s. pv. morsprunorum race 1. Simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
3
4
0
Order By: Relevance
“…were cultivated, disease symptoms were detected only on V. Chkalov, Summit, B. Burlat and N. Star (which were rated as highly susceptible). Occurrence of bacterial spots on sweet cherries in a few locations in Vojvodina Province, Serbia, was reported earlier (Balaž et al, ; Iličić, ; Iličič, Balaž, et al, ). Bacterial spot can affect 15%–40% of sweet cherry leaves, and cvs.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…were cultivated, disease symptoms were detected only on V. Chkalov, Summit, B. Burlat and N. Star (which were rated as highly susceptible). Occurrence of bacterial spots on sweet cherries in a few locations in Vojvodina Province, Serbia, was reported earlier (Balaž et al, ; Iličić, ; Iličič, Balaž, et al, ). Bacterial spot can affect 15%–40% of sweet cherry leaves, and cvs.…”
Section: Discussionsupporting
confidence: 54%
“…Obtained isolates were tested for different biochemical characters: Gram reaction; presence of catalase; production of fluorescent pigment on King B medium; oxidative-fermentative metabolism of glucose; LOPAT and GATTa tests (Latorre & Jones, 1979;Lelliott & Stead, 1987;Lelliott et al, 1966). Molecular identification was based on the detection of genes for discriminative bacterial toxin production or synthesis, namely: coronatine production gene (cfl) using Primer1/2 primer set (Bereswill et al, 1994) and genes for syringomycin synthesis (syrB) and syringomycin secretion (syrD) by two sets of primers, B1/B2 and SyD1/SyD2 (Iličič, Balaž, et al, 2016). The reference strains KFB0120 (pv.…”
Section: Field Conditions-natural Infectionmentioning
confidence: 99%
“…Most phenotypic tests such as Gram staining, fluorescent pigmentation on KB medium and LOPAT were similar to strains previously reported (Mohammadi et al 2001;Natalini et al 2006;Ilicic et al 2016). In this study, strains isolated from barley could not produce levan polymers.…”
Section: Discussionsupporting
confidence: 89%
“…Syringomycin is an important bacterial phytotoxin with a number of syr genes involved in regulation (syrA, syrF, syrG and salA), biosynthesis (syrB1, syrB2, syrC and syrE) and secretion (syrD and syrP) (Bender et al 1999;Vaughn and Gross 2016;Adbellatif et al 2017). Pss strains were compared with each other on the basis of syrB, syrC and syrD genes (Natalini et al 2006;Gasic et al 2012;Ivanovic et al 2012;Ilicic et al 2016). In this study, we found a correlation between syringomycin production in vitro and amplification of syrB (752 bp) and syrD (446 bp) genes.…”
Section: )supporting
confidence: 55%
“…P. syringae pv. syringae can infect an extensive host range of monocotyledonous and dicotyledonous plants (Iličic et al, 2016;Choi et al, 2017). P. syringae pv.…”
Section: Introductionmentioning
confidence: 99%